Fundamental Analysis of Firm Performance of Publicly Listed Manufacturing Companies in Indonesia - Yesi Dwitama; Elizabeth Sugiarto Dermawan (International Journal of Application on Economics and Business, 2023)
The study was carried out with the goal of obtaining empirical evidence about the fundamental analysis factors in the form of financial ratio, sales growth, and firm size that affect firm performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2019. This study used financial statement data from the IDX's official page and the firm's official page. The purposive sampling technique was used in this study, with a total of 178 samples from manufacturing sector companies. SPSS 17 and Microsoft Excel 2010 software were used to process and test the data. According to the findings of this study, capital structure and sales growth has no negative significant effect on firm performance, while sales growth and Total Asset Turnover Ratio has a positive significant effect on firm performance.